Do patients or their physicians more accurately assess long-term risk associated with hypertension? A population-based study - Mikael Hoffmann; Peter M. Nilsson; Johan Ahlner; Björn Dahllöf; Mats Fredrikson; Roger Säljö; Karin I. Kjellgren (Taylor & Francis Group, 2020)
Objective: To compare the assessments of 10-year probability by patients and their physicians of cardiovascular complications of hypertension with actual outcomes. Design: Patients with uncomplicated hypertension treated with at least one antihypertensive drug at inclusion were followed for 10 years through mandatory national health registers. Setting: 55 primary health care centres, 11 hospital outpatient clinics in Sweden Patients: 848 patient, 212 physicians. Main outcome measures: Patients and physicians estimated the probability of hypertension-related complications with treatment (death, heart failure, acute myocardial infarction/AMI, and stroke) for each patient in 848 pairs. Estimates were compared with the clinical outcomes 10 years later using data from the Mortality Register and the National Patient Register. Results: Patients were significantly better (p < 0.001) than their physicians in estimating the average probability of heart failure compared with actual outcome data (14% vs. 24%, outcome 15%), AMI (16% vs. 26%, outcome 8%), and stroke (15% vs. 25%, outcome 11%). Patients were significantly worse (p < 0.001) at estimating the average probability of death (10% vs. 18%, actual outcome 20%). Neither the patients nor the physicians were able to distinguish reliably between low-risk and high-risk patients after adjustment for age and sex. Conclusions: Patients were better than their physicians in estimating the average probability of morbidity due to hypertension. Both the patients and their attending physicians had difficulty in estimating the individual patient's risk of complications. The results support the use of evidence-based tools in consultations for assessing the risk of cardiovascular complications associated with hypertension.Key points  • Shared decision making relies on a common understanding of risks and benefits. Tools for risk assessment of hypertension have been introduced in the last two decades.  • Without tools for risk assessment, both patients and physicians had difficulties in estimating the individual patient's risk of cardiovascular morbidity.  • Patients were better than physicians in estimating actual average cardiovascular morbidity due to hypertension during a follow-up of 10 years.  • The results support the use of evidence-based tools in consultations for assessing the risk of cardiovascular complications associated with hypertension.